2014
DOI: 10.1159/000368020
|View full text |Cite
|
Sign up to set email alerts
|

2014 KLCSG-NCC Korea Practice Guidelines for the Management of Hepatocellular Carcinoma: HCC Diagnostic Algorithm

Abstract: Hepatocellular carcinoma (HCC) is the fifth most commonly occurring cancer in Korea and typically has a poor prognosis with a 5-year survival rate of only 28.6%. Therefore, it is of paramount importance to achieve the earliest possible diagnosis of HCC and to recommend the most up-to-date optimal treatment strategy in order to increase the survival rate of patients who develop this disease. After the establishment of the Korean Liver Cancer Study Group (KLCSG) and the National Cancer Center (NCC), Korea jointl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 143 publications
0
62
0
Order By: Relevance
“…Some studies show SPIO-enhanced MRI is less efficient than standard Gadolinium-enhanced dynamic MRI in the detection and characterization of HCC (122). Currently, hepatocyte-specific contrast agent Gd-EOB-DTPA (Primovist ® , Europe; Eovist ® , USA; Bayer HealthCare) enhanced liver MRI is emerging as the leading method for diagnosis and staging of HCC (123). Moreover, Nishie et al (124) reported that the uptake of Gd-EOB-DTPA in the liver parenchyma decreased as the liver fibrosis progressed, however, no significant correlation was obtained between the parameters on Resovist ® -enhanced MRI and the histological findings of the liver parenchyma.…”
Section: Spio Enhanced Liver Mrimentioning
confidence: 99%
“…Some studies show SPIO-enhanced MRI is less efficient than standard Gadolinium-enhanced dynamic MRI in the detection and characterization of HCC (122). Currently, hepatocyte-specific contrast agent Gd-EOB-DTPA (Primovist ® , Europe; Eovist ® , USA; Bayer HealthCare) enhanced liver MRI is emerging as the leading method for diagnosis and staging of HCC (123). Moreover, Nishie et al (124) reported that the uptake of Gd-EOB-DTPA in the liver parenchyma decreased as the liver fibrosis progressed, however, no significant correlation was obtained between the parameters on Resovist ® -enhanced MRI and the histological findings of the liver parenchyma.…”
Section: Spio Enhanced Liver Mrimentioning
confidence: 99%
“…Seven out of these 8 lesions were diagnosed by gadobenate dimeglumine-enhanced MRI (multihance) as HCC, showing hyperintensity in the arterial phase and hypointensity in the HBP (according to the latest guidelines for diagnosis of HCC including those of the Japan Society of Hepatology (JSH), [12] the Korean Liver Cancer Study Group (KLCSG), the National Cancer Center (NCC), [13] and the Liver Imaging Reporting and Data System (LI-RADS).…”
Section: Discussionmentioning
confidence: 99%
“…However, for optimal screening examination results, high-quality imaging studies are also crucial. US surveillance of HCC every six months in populations at an elevated risk has been proven to reduce HCC related deaths and is recommended as a standard protocol in many countries, including the United States, Europe, Japan, and Korea [6][7][8][9][10]. Recent guidelines for the management of HCC from the American Association for the Study of Liver Disease (AASLD) and the European Association for the Study of Liver (EASL) recommended maintaining high-quality US examinations for optimal surveillance [6,7].…”
Section: Discussionmentioning
confidence: 99%